RADIAL HEAD RESCTION - IS IT STILL VALUABLE SURGICAL SOLUTION? - Spasov, Marko; Mirceska Arsovska, Elena; Damcevska, Jadranka; Krstevski, Stefan; Kaftandziev, Igor (Journal of Morphological Sciences; Vol 3 No 1 (2020): JMS, 2020)
The aim of the present study was to review the functional and radiological results following the traditional technique on radial head resection for unreconstructable radial head fractures.Clinical evaluation included the Disabilities of the Arm, Shoulder and Hand questionnaire. Elbow pain was graded as none, mild, moderate or severe. A visual analogue scale was used for the assessment of patient satisfaction. We assessed the difference in the strength between both sides, valgus laxity of the elbow, posterolateral instability and grip strength. On the basis of the interview and the physical examination, Mayo Elbow Performance S was evaluated. Radiographic review consisted of evaluating for proximal migration of the radius, radial shortening and ulnar variance.  21 patents with a mean age of 36 years at the time of injury that underwent radial head resection were included. The mean value of Visual Analogue Scale satisfaction score was 9 (range 4-10; Std =1.54). Mean range of motion was 9° of extension (range 0° to 32°) and 135° of flexion (range 70° to 145°). Mean total arc was 130° (range 70° to 145°). Eighteen patients (86%) had a functional arc of motion (≤30° to ≥130°). Mean value of MEPS was 95 points (range 60-100 points; Std=8.76). Increased ulnar variance was 17 patients. Three patients had proximal migration of the radius (> 5mm). Our data suggest that comminuted fractures of the radial head may be treated with radial head excision with satisfactory long-term functional outcome. Despite popularity of radial head prostheses, good functional result can be obtained even without radial head replacement. Keywords:radial head, fracture, resection, outcome.